PENGARUH KECERDASAN EMOSIONAL DAN PERSEPSI IKLIM ORGANISASI TERHADAP KINERJA GURU - Elin 1, Ani Interdiana Candra Sar Karlina (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Abstract The reseach aims to get empric answer about: (1) emotional intelectual to performance,(2) organizational climate perseption on performance, (3) emotional intelectual and organization climate perseption to performance. The reseach was done in hight school in east Jakarta with 50 teachers as responden. The method of this reseach is survey with regression approach. From this reseach result and SPSS account found:(1)There is an effect of emotional intelligence on the performance of teachers. (2) There is an effectperceptions oforganizational climateon teacher performane. (3)Thereisaneffect ofemotional intelligenceand perceivedorganizational climateon the performance ofteachers. Organizational climate variable has significant impact to teacher’s performance enhancement. A good Organizational climate and stimulatee motional intelligencethat can ultimat elyimprove teacher performance. Keywords: Emotional Intelectual, Perseption of organizational Climate Perseption,and Teachre’s Performance